TRANSAKSI MELALUI ATM DITINJAU DARI HUKUM ISLAM - Deery Anzar Susanti (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study aims to see the concept of transactions using ATMs, in terms of Islamic law. The development of Islamic financial institutions in Indonesia has increased significantly, this certainly encourages the desire of Islamic financial institutions to keep moving forward with the times. One of the developments that continues to be initiated by Islamic financial institutions is the use of electronic transactions and automated teller machines. This research is a qualitative research, by checking the validity of the data using a literature review.